The plot to save South Africa : the week Mandela averted civil war and forged a new nation - Malala, Justice (Simon & Schuster, 2023)
"A riveting, kaleidoscopic account of nine days in the life of a country on the edge, as the assassination of Nelson Mandela's protégé by a white supremacist threatens to derail South Africa's democratic transition and plunge the nation into civil war"--